Clinical Usefulness of HRCT in Assessing the Severity of Pneumocystis jirovecii Pneumonia. Issue 16 (April 2015) - Chou, Chung-Wei; Chao, Heng-Sheng; Lin, Fang-Chi; Tsai, Han-Chen; Yuan, Wei-Hsin; Chang, Shi-Chuan; Yong., Tuck Yean
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to investigate the clinical relevance of thoracic high-resolution computed tomography (HRCT) in evaluating the severity and outcome of Pneumocystis jirovecii pneumonia (PJP) in non-AIDS immunocompromised patients. We measured mean lung attenuation (MLA) and extent of increased attenuation (EIA) of PJP lesions on thoracic HRCT in 40 non-AIDS immunocompromised patients with PJP diagnosed by demonstration of the pathogens in cytological smears of bronchoalveolar lavage fluid. The MLA and EIA of PJP lesions on thoracic HRCT were used to investigate the severity of PJP. Clinically, the severity of PJP was determined by arterial oxygen tension/fraction of inspired oxygen concentration (PaO2/FiO2) ratio, acute physiology and chronic health evaluation (APACHE) II scores, the need of mechanical ventilation, and death. MLA highly correlated with EIA of PJP lesions (ρ = 0.906, P < 0.001). MLA and EIA of PJP lesions significantly correlated with PaO2/FiO2 (ρ = −0.481 and −0.370, respectively and P = 0.007 and 0.044, respectively). When intensive care unit (ICU) admission and HRCT performed were within 2 days, MLA and EIA of PJP lesions were significantly correlated with APACHE II score (ρ = 0.791 and 0.670, respectively and P = 0.001 and 0.009, respectively). There were significant differences in the values of MLA and EIA of PJP lesions between patients with and without assisted mechanical ventilator (MLA, median and [interquartile range, IQR, 25%, 75%] −516.44 [−572.10, −375.34] vs −649.27 [−715.62, −594.01], P < 0.001 and EIA, median and [IQR 25%, 75%] 0.75 [0.66, 0.82] vs 0.53 [0.45, 0.68], P = 0.003, respectively). The data of MLA and EIA of PJP lesions had limited value in identifying survivors and non-survivors. The MLA and EIA values of PJP lesions measured on thoracic HRCT might be valuable in assessing the severity of PJP in non-AIDS immunocompromised patients, but might have limited value in predicting the mortality of the patients.